OPTIMIZING THE SUCCESS OF LEARNING IN MEETING MANAGEMENT SUBJECTS THROUGH CANVA MEDIA IN VOCATIONAL SCHOOLS - Alfian, Muhammad; Marsofiyati; Wolor, Christian Wiradendi (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2024)
This study aims to develop canva-based learning media in the subject of Meeting Management Phase F Office Management (MP) Public Vocational High School 46 Jakarta. The research method used in this research is RnD (Research and Development). The population in this study amounted to 35 students of Phase F MP Public Vocational High School 46 Jakarta. The data analysis techniques used in this study are qualitative analysis and quantitative analysis. Qualitative techniques are used to analyze data in the form of notes, suggestions, or comments from the assessment of validation sheets or questionnaires from the assessment of validators and trial subjects. The results of this study are based on the results of validation tests from several experts, namely material experts, linguists, and media experts, that the canva-based learning media developed obtained an average percentage of 91% with a very feasible category.